2013
DOI: 10.3390/ijms140815767
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Caspase-3 Expression in the Adjacent Areas of Growth Plate Injury Site: A Morphological Study

Abstract: The epiphyseal plate is a hyaline cartilage plate that sits between the diaphysis and the epiphysis. The objective of this study was to determine the impact of an injury in the growth plate chondrocytes through the study of histological morphology, immunohistochemistry, histomorphometry and Western Blot analyses of the caspase-3 and cleaved PARP-1, and levels of the inflammatory cytokines, Interleukin-6 (IL-6) and Tumor Necrosis Factor alpha (TNF-α), in order to acquire more information about post-injury react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…5A, fifth cluster from top). Notably, D7 f-BCSPs down-regulated the following apoptotic factors: B-cell leukemia/lymphoma 10, Caspase3, Dido1, Mitochondrial ubiquitin ligase activator 1, and Cell division cycle and apoptosis regulator 1 (22,23). These data support reduced f-BCSP apoptotic activity seen in Fig.…”
Section: Significancesupporting
confidence: 76%
“…5A, fifth cluster from top). Notably, D7 f-BCSPs down-regulated the following apoptotic factors: B-cell leukemia/lymphoma 10, Caspase3, Dido1, Mitochondrial ubiquitin ligase activator 1, and Cell division cycle and apoptosis regulator 1 (22,23). These data support reduced f-BCSP apoptotic activity seen in Fig.…”
Section: Significancesupporting
confidence: 76%
“…Macsai et al (2011) also observed that the adjacent growth plate showed decreases in expression of chondrogenic transcription factor Sox9 and growth factors TGFB1 and IGF1 in comparison to their non-injured controls (Macsai et al 2011). Similarly, Musumeci et al (2013) also reported an increase in expression of apoptotic marker, caspase-3 protein, over days 7-30 post-injury in the adjacent growth plate of their experimental rats (Musumeci et al 2013), although this study did not use an antibody that distinguishes between the intact inactive and cleaved active forms of caspase-3. Musumeci et al (2013) suggest that one potential mechanism for this histomorphological change at the adjacent growth plate may be related to the observed increase in levels of inflammatory cytokine TNFa during the bony repair tissue formation at the growth plate injury site (Musumeci et al 2013).…”
Section: Potential Changes At the Adjacent Non-injured Region Of The mentioning
confidence: 95%
“…Similarly, Musumeci et al (2013) also reported an increase in expression of apoptotic marker, caspase-3 protein, over days 7-30 post-injury in the adjacent growth plate of their experimental rats (Musumeci et al 2013), although this study did not use an antibody that distinguishes between the intact inactive and cleaved active forms of caspase-3. Musumeci et al (2013) suggest that one potential mechanism for this histomorphological change at the adjacent growth plate may be related to the observed increase in levels of inflammatory cytokine TNFa during the bony repair tissue formation at the growth plate injury site (Musumeci et al 2013). While the above studies have demonstrated that the growth plate injury also affects the uninjured adjacent areas of growth plate, the current evidence is quite limited.…”
Section: Potential Changes At the Adjacent Non-injured Region Of The mentioning
confidence: 99%
“…OA is a chronic disease characterized by degenerative and productive changes of the joints (Figure 2) [28] . It is essentially linked to an imbalance between excessive cartilage damage and the ability of cartilage to "heal", but involves and compromises the whole joint, in all its aspects, both macroscopic and microscopic changes (Figure 2) [29][30][31] . Risk factors include age [32,33] , mechanical factors [33] , obesity [34] , and inflammation [35,36] .…”
Section: Rheumatic Diseasesmentioning
confidence: 99%